Az elektronikus közigazgatás stratégiai kérdései az Európai Unióban - Ravasz, Péter (Debreceni Jogi Műhely, 2018)
Radical changes could be observed at the of the 20th century and can also be found especially in the 21st century regarding the electronic administrative procedure both in the European Union and in the Member States. These changes primarily originate from the technical development, to which administration has to reflect; furthermore administration should be more faster and can be made closer to the citizens. I review the European Union's strategies and priorities concerning electronic administration in this paper. The European Union's powers are mainly focused on the implementation of such services in all Member States approximately at the same time in this field, if possible on the same technical grounds because only this way can the real interoperability between the different systems be guaranteed. But the interoperability of the national administrations is significantly limited by the linguistic diversity of the European Union because in the absence of a common official langugae real interoperability is limited by the different official languages used in the Member States. Such fields are for example the company registers and its accessibility through the European e-Justice Portal. Although, the efforts for e-administratation of the European Union do not cover all areas of the national administrations, furthermore while the European Union's regulation is focused on the economically efficient activites, Member States have to prioritise issues of citizens' and legal persons' everyday lives when creating and realising eloctronic administration.